Note:
Your first question is missing the y-intercept, so I am solving the 2nd question, but the procedure to solve each of the questions is the same.
Answer:
The equation in the standard form is:
[tex]\frac{2}{3}x\:+\:y\:=-4[/tex]
Step-by-step explanation:
Given
Slope m = -2/3
y-intercept = -4
We know that the slope-intercept form of the line equation
y = mx+b
where
now substituting m = -2/3 and y-intercept b = -4 in the slope-intercept of the line equation
[tex]y = mx+b[/tex]
[tex]y\:=\:-\frac{2}{3}x\:\:+\:\left(-4\right)[/tex]
[tex]y\:=\:-\frac{2}{3}x\:-4[/tex]
We know that the equation in the standard form is
[tex]Ax + By = C[/tex]
where x and y are variables and A, B and C are constants
so writing the equation in the standard form
[tex]y\:=\:-\frac{2}{3}x\:-4[/tex]
[tex]\frac{2}{3}x\:+\:y\:=-4[/tex]
Therefore, the equation in the standard form is:
[tex]\frac{2}{3}x\:+\:y\:=-4[/tex]